GC-Derived EVs Enriched with MicroRNA-675-3p Contribute to the MAPK/PD-L1-Mediated Tumor Immune Escape by Targeting CXXC4 - Ping Li; Xingdong Luo; Yue Xie; Pengfei Li; Fangyong Hu; Junfeng Chu; Xiaojun Chen; Wenbo Song; Ali Wang; Guangyu Tian; Xiang Gu (Elsevier, 2020)
MicroRNAs (miRNAs) delivered by gastric cancer (GC)-secreted extracellular vesicles (GC-EVs) are associated with the immune escape in GC. Microarray analysis based on the GEO: GSE112369 dataset identified the presence of poorly expressed CXXC finger protein 4 (CXXC4) in GC, which was validated in clinical samples of GC patients. Moreover, prediction based on TargetScan analysis demonstrated the putative miR-675-3p binding site in the 3' UTR region of CXXC4. Thereby, our study aims to determine the role of GC-EV-encapsulated miR-675-3p in GC. First, CXXC4 was found to be negatively correlated with programmed cell death 1 ligand 1 (PD-L1). The effects of mitogen-activated protein kinase (MAPK) signaling on GC were evaluated using activator of the MAPK pathway. The overexpression of CXXC4 led to a downregulated MAPK signaling pathway, thus decreasing PD-L1 expression to augment the proliferation and activation of T cells co-cultured with GC HGC-27 cells. GC-EV-encapsulated miR-675-3p negatively regulated the expression of its target gene CXXC4. GC-EV-encapsulated miR-675-3p increased PD-L1 expression to stimulate the immune escape in vitro and EV-encapsulated miR-675-3p accelerated cisplatin resistance in vivo. Collectively, the aforementioned findings present a mechanism in which EV-mediated miR-675-3p upregulates PD-L1 expression, promoting immune escape in GC.